William J. Gedney's Comparative Tai Source Book - Hudak, Thomas John (University of Hawaii Press, 2007)
This volume provides accurate and reliable data from 1,159 common cognates found in 19 dialects from the Tai language family. Originally collected by noted Tai linguist, the late William J. Gedney, the data are organized into the three branches of the Tai language family, the Southwestern, the Central, and the Northern, to facilitate comparisons among the various sound systems within the individual branches and within the Tai language family as a whole. Supplementing the cognates are phonological descriptions of each of the dialects. Included among the nineteen dialects are Siamese, White Tai, Black Tai, Shan, Lue, Yay, Saek, and dialects found at Leiping, Lungming, Pingsiang, and Ningming in China. The meticulous attention paid to consonants, vowels, and tones found in each cognate will allow for further dialect studies, for the investigation of questions concerning the tripartite division of the Tai language family, and for the continuing investigation into the reconstruction of the Proto-Tai language family and its wider genetic relationships.